SUBJECTION AND RECOGNIZABILITY: AGAINST RECOGNITION’S INNOCENCE IN AXEL HONNETH - Gorriti, Jacinta (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
This article presents a critical reading of Axel Honneth’s work “Recognition as ideology” (2006), built upon Judith Butler’s theory of subjection. It attempts to show that because of not considering here enough the dimension of power, the German thinker does not confront successfully the stances that question recognition’s critical potential. This work suggests that such an absence is linked to Honneth’s definition of recognition as being the opposite of practices of domination or subordination. However, Honneth affirms that these skeptical stances are based on the idea that every recognitional praxis reproduces in some way the dominating social order. This article offers then, a critical look upon this idea, warning that an analysis about the way power works on daily recognition practices does not necessarily entail a resignation of the critical function of recognition. More likely, as the Butlerian (and Foucauldian) notion of critique suggests, only by framing recognition in the normative horizon that defines it, it can become the basis of social inquiry.